Does interdisciplinarity lead to higher employment growth of academic spinoffs? - Bettina Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Does heterogeneity in the educational backgrounds of the founders matter for firm success? Are team foundations more successful than single entrepreneurs? These questions are analysed using data on academic spinoffs in Germany. Firm success is measured by employment growth. I find that team foundations have higher employment growth than single entrepreneurs. Team foundations of engineers perform better when they have a business scientist in the team. However, different subjects per se and heterogeneity in the academic origins of the founders do not play a significant role for the employment growth of academic spinoffs.
Keywords: C12; L25; M13; 330; human capital; entrepreneurship; academic spinoffs; employment growth; Unternehmensgründung; Forschungskooperation; Betriebsaufspaltung; Unternehmer; Akademische Berufe; Interdisziplinäre Forschung; Erfolgsfaktor; Beschäftigungseffekt; Deutschland